Morbi-mortality of lower respiratory tract infections in Spain, 1997-2018 - Leache, L; Gutiérrez-Valencia, M; Saiz, L C; Erviti, J (Anales del sistema sanitario de Navarra, 2021)
Lower respiratory tract infections (LRTIs) are one of the leading causes of infectious disease mortality worldwide. The aims of the study were to determine the incidence of hospitalizations due to LRTIs, and to analyze the clinical outcomes of the hospitalized patients. An observational study of hospitalizations due to LRTIs (pneumonia and acute bronchitis/bronchiolitis) in Spain from 1997 to 2018 was carried out. Data were extracted from the national information system for hospital data. Overall, 3.5% (IQR: 3.4-3.5%) of total hospitalizations were caused by LRTIs, with a median incidence of 31.2 (IQR: 27.8-33.0) per 10,000 inhabitants/year. The median incidence was higher for pneumonia than for acute bronchitis/bronchiolitis cases (22.2; IQR: 19.1-23.5 vs. 9.0; IQR: 8.4-9.6 per 10,000 inhabitants/year; p<0.001) and increased by 65.7% from 1997 to 2018. A 41.2% of the hospitalizations due to LRTIs took place amongst people over 74 years. The median length of stay was 8.9 days (IQR: 7.6-10.4) and was higher for hospitalizations due to pneumonia than for acute bronchitis/bronchiolitis (9.5 days; IQR: 8.3-10.6 vs. 5.7; IQR: 5.5-6.2; p<0,001). In 89.1% of total hospitalizations due to LRTIs, patients were discharged home. In-hospital mortality was 6.8%, with 9,380 deaths (IQR: 8,192-10,157) per year. Mortality was higher for pneumonia (9.0 vs. 1.7%; p<?0.001) and doubled from 1997 to 2018 (5,257 deaths in 1997 and 10,514 in 2018). The 75.5% of the deaths occurred amongst people over 74 years. LRTIs are associated with a high morbi-mortality in Spain. Effective measures that can contribute towards the prevention and treatment of LRTIs need to be adopted.